PEMBUATAN KARBOKSIMETIL SELULOSA DARI KULIT PISANG KEPOK DENGAN VARIASI KONSENTRASI NATRIUM HIDROKSIDA, NATRIUM MONOKLOROASETAT, TEMPERATUR DAN WAKTU REAKSI - Saputri Ayuningtiyas, Feni Dwi Desiyana, Siswarni MZ (Universitas Sumatera Utara, 2017)
Carboxymethyl cellulose (CMC) is a derivative cellulose which is soluble an in water (hydrophilic colloid). This material effective to bind water to provide a uniform texture and increase viscosity. The aim of this study is to utilize banana peel as a raw material to synthesis CMC and determine the best conditions in the process of synthesis CMC from banana peel. The materials used were banana peel, water, aquades, NaOH, Natirum monochloroacetat and glacial acetic acid. The variables in this study were NaOH concentration, natirum monochloroacetat mass, temperature and reaction time. In this research consists of four stages there are preparation of raw materials, alkalization, carboxymethylation, and neutralization. The results of this research shows the variatioon NaOH concentration 20% and temperature of 45oC degree, mol rasio of cellulose:sodium monochloroacetat 1:1,6 with a reaction time of 120 minutes obtained the highest substitution degree of 0,73-0.812. The FTIR analysis shows the presence of the O-H, C-H, C = O, C-0, CH2 and 1,4 β-glycoside function groups known to have the same function groups as the commercial carboxymethyl cellulose.